Principal Leadership, Teacher Competence, and Teacher Performance: Investigating the Moderating Effect of Artificial Intelligence (AI) Utilization at SMAN 1 Manyar - Muafiah Muafiah; Noor Hudallah; Arief Yulianto; Suwito Eko Pramono; Sungkowo Edy Mulyono (Yayasan Vifada Cendikia Indonesia, 2026)
This study aims to examine the effects of principal leadership and teacher competence on teacher performance, as well as the moderating role of Artificial Intelligence (AI) utilization at SMAN 1 Manyar Gresik. It hypothesizes that principal leadership and teacher competence positively influence teacher performance, while AI utilization strengthens these relationships. A quantitative correlational design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) based on data collected from 65 teachers, supported by interviews to enrich contextual understanding. The results indicate that principal leadership significantly improves teacher competence (β = 0.477; p < 0.001), while teacher competence positively affects teacher performance (β = 0.280; p = 0.025). However, principal leadership does not directly influence teacher performance (β = -0.008; p = 0.955), and AI utilization has no significant direct effect (β = 0.217; p = 0.073). AI also fails to moderate the relationship between principal leadership and teacher performance but significantly and negatively moderates the relationship between teacher competence and teacher performance, suggesting an equalizer technology effect. These findings imply that improving teacher performance depends primarily on strengthening teacher competence through effective school leadership, while AI integration requires more strategic implementation. Future research should explore broader educational contexts and additional factors influencing AI adoption and teacher performance